2017
DOI: 10.4236/cweee.2017.61003
|View full text |Cite
|
Sign up to set email alerts
|

Application of SWAT to Assess the Effects of Land Use Change in the Murchison Bay Catchment in Uganda

Abstract: The Soil and Water Assessment Tool (SWAT) is a versatile model presently used worldwide to evaluate water quality and hydrological concerns under varying land use and environmental conditions. In this study, SWAT was used to simulate streamflow and to estimate sediment yield and nutrients loss from the Murchison Bay catchment as a result of land use changes. The SWAT model was calibrated and validated for streamflow for extended periods. The Sequential Uncertainty Fitting (SUFI-2) global sensitivity method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…The sensitivity analysis from other watersheds in the East African region had, among the top six sensitive parameters, few parameters similar to the one found in the Ndembera watershed. For example, in Murchison Bay Catchment, Uganda, the CN_2, GW_DELAY and GW_REVAP were among the top six sensitive parameters to river discharge (Anaba et al 2017). The CN_2 and SOL_AWC were also among the most sensitive parameters reported in the Simiyu river Catchment in Tanzania (Mulungu and Munishi 2007).…”
Section: Model Parameterization and Sensitivity Analysismentioning
confidence: 95%
“…The sensitivity analysis from other watersheds in the East African region had, among the top six sensitive parameters, few parameters similar to the one found in the Ndembera watershed. For example, in Murchison Bay Catchment, Uganda, the CN_2, GW_DELAY and GW_REVAP were among the top six sensitive parameters to river discharge (Anaba et al 2017). The CN_2 and SOL_AWC were also among the most sensitive parameters reported in the Simiyu river Catchment in Tanzania (Mulungu and Munishi 2007).…”
Section: Model Parameterization and Sensitivity Analysismentioning
confidence: 95%
“…Urbanisation has caused a significant negative impact on the environment in the catchment as it has created permanent impervious layers which reduces infiltration and percolation of water to the underground increasing surface runoff and causing perennial flooding within the catchment. Wastewater and other pollutants discharged from industrial setup have also increased the quantity of sediments and nutrients transported into the Lake Victoria from the catchment studied (Anaba et al, 2017). Encroachment on wetlands that have for long acted as filters and traps pollution discharges from the catchment (JTR, 2015; Kansiime & Nalubega, 1999) area have lost its function as a buffer zone.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the runoff is intensified towards drainage lines. Anaba et al (2017) used the SWAT model in various land use scenarios and found that The model satisfactorily simulated stream discharge from the catchment. The model performance was determined with different statistical methods.…”
Section: Validationmentioning
confidence: 99%